Anti-Inflammatory Activity Of Eugenia Jambolana In Albino Rats - PAVAN KUMAR. KOTA; DHARANI PRASAD. P; NARAYANA RAO. A; DAYAKAR REDDY. P; G. ABHINAY (International Journal of Pharma and Bio Sciences, 2010)
Objectives: To study the anti-inflammatory activity of Eugenia Jambolana leaves extract in albino rats. Methods: Leaves of Eugenia Jambolana were extracted and the extract was screened for antiinflammatory activity in albino rats using acute carrageenan paw oedema and chronic granuloma pouch model. Results: The extract showed presence of chemical compounds with hydroxyl, ester, carbonyl and olefin functionalities and exhibited dose dependant anti-inflammatory activity in acute and chronic models. Conclusions: The extract of Eugenia Jambolana leaves showed anti-inflammatory activity in acute and chronic administration in albino rats.